For Better or worse: Organizational turnaround in New York City schools. Issue 3 (15th March 2016) - Favero, Nathan; Rutherford, Amanda
Abstract: The performance of public organizations has become a more salient issue as the popularity of accountability policies has grown. Though organizations are often defined as underperforming, little is known about the effectiveness of various strategies commonly recommended for agency turnaround. This study provides a large-N test of three common categories of turnaround mechanisms – retrenchment, repositioning, and reorganization – in nearly 300 failing New York City schools between 2008 and 2011. Models show that none of the three turnaround strategies appear to be significantly associated with improvements in core organizational performance from an administrative perspective, although repositioning appears to improve client satisfaction.